The Brazilian G2P model: digital transformation in times of the COVID-19 pandemic - Vieira , Thays Cintra; Streit , Rosalvo Ermes; da Silva, Ana Paula Bernardi (Revista Gestão do Conhecimento e Tecnologia da Informação, 2025)
Purpose: This study analyzes the digital government-to-person (G2P) model adopted in Brazil during the COVID-19 pandemic, focusing on three key areas: (i) digital transformation strategies implemented, (ii) beneficiary use of digital accounts, and (iii) perceptions of managers at the financial institution responsible for program delivery. Methodology: The research employed a pragmatic approach, combining document analysis, operational and transaction data collection, and qualitative interviews with managers from the public financial institution executing the program. Results: Key success factors identified include the institution’s prior experience in managing social programs and coordinating with a broad network of partners, the functionality and user-friendliness of the mobile application developed specifically for the transfers, and the implementation of a payment schedule that supported operational organization and risk mitigation. Practical/managerial implications: The findings provide valuable insights for improving public policies that leverage digital cash transfer models. The results highlight the importance of investing in technological infrastructure, digital governance, and institutional capacity building to support large-scale social payment operations. Social implications: The adoption of the digital G2P model not only enabled the efficient distribution of emergency funds during the health crisis but also fostered financial inclusion for millions of Brazilians previously excluded from the formal financial system, contributing to a structural shift in how these citizens engage with digital financial services.